Occupational change and status mobility - Arne Bethmann (Journal for Labour Market Research, 2013)
The impact of changes of the occupational field on the socio-economic status after unemployment has not received much attention in the literature so far. Due to a possible loss of occupation specific human capital the effects are assumed to be detrimental. This seems especially probable if the individual has attained specific human capital in the form of vocational training. A sample from the panel study 'Labour Market and Social Security' (PASS) was used to analyse the occupational changes of unemployed individuals upon re-entry into the labour market. Compared to occupational changes from employment, changes in the unemployment group have stronger negative effects on the difference in socio-economic status between the last and the current job. The International Socio-Economic Index (ISEI) was used as the status measure. For unemployed individuals without vocational training no significant effect could be found, whereas those with training did incur substantial status losses. In conclusion the loss of occupation specific human capital due to changes of occupation does seem to be detrimental to the socio-economic situation of unemployed individuals after re-employment. This should be considered when applying strict labour market policies possibly pressuring individuals to change their occupation in order to take up employment more quickly.
Keywords: J62; J44; 330; Arbeitslosigkeit; Dequalifizierung; Berufswechsel - Auswirkungen; sozialer Status; Statusmobilität; beruflicher Status; berufliche Reintegration; Arbeitslose; IAB-Haushaltspanel; sozioökonomische Faktoren; sozialer Abstieg; beruflicher Abstieg